Differential diagnosis of a local form of granulomatosis with polyangiitis: ocular and ear involvement (part 2) - O. N. Egorova; E. N. Kharlamova; G. M. Tarasova (Современная ревматология)
Granulomatosis with polyangiitis (GPA) is a primary vasculitis associated with antineutrophil cytoplasmic antibodies, characterized by necrotizing vasculitis with predominant involvement of small vessels of various localization and necrotizing granulomatous inflammation with multiple clinical manifestations. GPA remains one of the most severe and prognostically unfavorable systemic vasculitis. The second part of the article presents data on the differential diagnosis of the onset of the disease with the ocular and ear involvement, which requires an interdisciplinary approach and interaction between doctors of different specialties. In the refractory course of the local form of GPA, immunosuppressive therapy, including glucocorticoids and rituximab or cyclophosphamide, is advisable.